Evidence of Cuticle Chemicals of Heortia vitessoides (Lepidoptera: Crambidae) Larvae Influencing the Aggregation Behavior of Conspecific Larvae - Xinya Yang; Guangsheng Li; Cai Wang (Insects)
Heortia vitessoides (Lepidoptera: Crambidae) is a severe pest of Aquilaria plants, which produce high-priced agarwood. The larval stage of this pest is gregarious, usually forming large aggregates during young instars and becoming solitary during the fifth instar. We hypothesize that the cuticle chemicals of young-instar H. vitessoides larvae could promote larval aggregating, whereas the cuticle chemicals of late-instar larvae would no longer attract young-instar larvae. In this study, two-choice tests were conducted to evaluate the effect of cuticle extracts of second- and fifth-instar H. vitessoides larvae on the aggregation preference of second-instar larvae. Results show that significantly more larvae aggregated on the leaves treated with the hexane extract of second-instar H. vitessoides larvae than on untreated leaves. However, the hexane extract of fifth-instar larvae had no significant effect on the aggregation preference of the second-instar conspecific larvae. Interestingly, acetone extracts of both second- and fifth-instar H. vitessoides larvae repelled the second-instar conspecific larvae throughout the 8 h experiment. Our study shows that cuticle chemicals of H. vitessoides larvae may play a role in the group dynamics of this pest, which may contribute to screening novel attractants and repellents for H. vitessoides. Detailed chemical analyses of the extracts and identification of the compounds involved in larval attracting and repelling would be valuable in future studies.